PREFERRED LEARNING STYLES AND SOFT SKILLS: THE MODERATING IMPACT OF GENDER AND RESIDENCE AREA - Kogilavani a/p Apadore; Ku Nur Ilyani Binti Ku Abd Aziz; Zam Zuriyati Mohamad; Meenah Ramasamy; Yamuna Rani Palanimally (Journal of Islamic, Social, Economics and Development, 2021)
This study aims to achieve three objectives. First, to determine the preferredlearning styles for final year undergraduate accounting students. Second, to examine the effectof learning styles on soft skills. Third, to test whether gender and geographical residence areaact as a moderator on the relationship between learning styles and soft skills. The preferredlearning styles consist of visual, auditory and kinaesthetic while students’ soft skills consist ofcommunication skill and critical thinking. Fleming’s Theory of Learning Style has beenapplied as the underlying theory. 300 undergraduate accounting students participated in thisstudy. Barsch’s Learning Styles Inventory and Malaysian Soft Skills Scale were used tomeasure students’ learning styles and soft skills attainment level respectively. Partial leastsquare structural equation modelling was executed to accomplish the objectives of this study.The result shows that the most preferred learning style is visual. All learning styles arestatistically significant on soft skills. The Geographic residence area strengthens the influenceof visual learning style on soft skills. This study contributes to the development in accountingeducation, lecturers’ teaching approach and student employability. Theoretically, this studyoffers a new path in the education research area by connecting learning styles and soft skills